Developing Environment–Based Materials to Teach Writing in Recount Texts - Fauziah Ratna Hapsari (AT-TA'LIM, 2015)
The tenth graders of State Senior High School 2 Semarang had problems to write their experiences. Unfortunately the existing materials were not appropriate to facilitate the learners to write recount texts. Hence, this study would like to develop environment – based materials to teach writing recount texts. It was inspired by the previous studies held by Gürsoy (2010) and Hauschild (2012). The materials were expected to improve learners’ writing competence of recount texts by applying topics which learners found in their daily lives, that is, environmental education. This study employed Research and Development design adapted from Borg and Gall (2003). The study found that applying the environment – based materials to teach writing recount texts gained positive effects. Moreover, the test of effectiveness reported significant improvement. The average score of pre-test was 48.94 and of post-test was 81.61. Therefore, English teachers are suggested to employ the materials. It is also necessary to conduct further studies to gain more positive effects toward teaching and learning process and to improve the learners’ writing competence. Keywords: Teaching writing; recount text; environment – based materials; contextual teaching and learningCopyright © 2015 by Al-Ta'lim All right reserved